Fungal biodegradation of the N-nitrosodimethylamine precursors venlafaxine and O-desmethylvenlafaxine in water. (March 2019) - Llorca, Marta; Castellet-Rovira, Francesc; Farré, María-José; Jaén-Gil, Adrián; Martínez-Alonso, Maira; Rodríguez-Mozaz, Sara; Sarrà, Montserrat; Barceló, Damià
Abstract: Antidepressant drugs such as Venlafaxine (VFX) and O -desmethylvenlafaxine (ODMVFX) are emerging contaminants that are commonly detected in aquatic environments, since conventional wastewater treatment plants are unable to completely remove them. They can be precursors of hazardous by-products, such as the carcinogenic N -nitrosodimethylamine (NDMA), generated upon water chlorination, as they contain the dimethylamino moiety, necessary for the formation of NDMA. In this study, the capability of three white rot fungi ( Trametes versicolor, Ganoderma lucidum and Pleurotus ostreatus ) to remove both antidepressants from water and to decrease NDMA formation potential was investigated. Furthermore, transformation by-products (TPs) generated along the treatment process were elucidated and also correlated with their NDMA formation potential. Very promising results were obtained for T. versicolor and G. lucidum, both being able to remove up to 100% of ODMVFX. In the case of VFX, which is very recalcitrant to conventional wastewater treatment, a 70% of removal was achieved by T. versicolor, along with a reduction in NDMA formation potential, thus decreasing the associated problems for human health and the environment. However, the NDMA formation potential remained practically constant during treatment with G. lucidum despite of the equally high VFX removal (70%). This difference was attributed to the generation of different TPs during both fungal treatments. For example, G. lucidum generated more ODMVFX, which actually has a higher NDMA formation potential than the parent compound itself. Graphical abstract: Image 1 Highlights: Fungal bioremediation of antidepressants venlafaxine and O -desmethylvenlafaxine. Study of transformation by-products and evaluation of NDMA formation potential. Removal of antidepressants between 70 and 100% by T. versicolor and G. lucidum. Reduction of NDMA formation potential. Abstract : Promising results of the bioremediation of venlafaxine and O -desmethylvenlafaxine antidepressants, with removals of 70% and decrease of 50% of the NDMA formation potential.